Optimisation of base station locations for wireless CDMA in cellular communication systems - Tan, Alan Yeow Loon (2008)
This thesis presents the work done on the optimisation of the base station locations for a CDMA cellular mobile communication systems using the simulated annealing (SA) technique and a Geographic Information System (GIS)-based digitized map. The Central Business District (CBD) in the southern part of Singapore is the case study of interest.